Aplicación del plan de acción para el mejoramiento de las buenas prácticas de inclusión laboral de personas con discapacidad en la empresa TECFOOD S.A. - Herrera Espinoza, Alejandra Jesenia (2017)
This report describes the implementation of an Action Plan for improving inclusion practices in the Company Tecfood SA, a company dedicated to industrial catering for staff with disabilities. Experiences, knowledge and challenges are described, as they were identified as well as how they were solved while applying different action plans. It also explains, in general, how the instrument was developed showing both qualitative and quantitative data, impacting in axes as planning, inclusion, equity and development. These axes allowed the plan develops and then to be implemented at company level including measuring and managing the people with disabilities. So psychological theories and laws that came together was also defined for approval of this plan that initially focused on what other mandated but was gradually being part of a model of comprehensive an integral management, which allows creating tools for personnel administration.